Teamwork on the fly - Edmondson, Amy C. (2012)
Suggests that in today's fast-moving ultracompetitive global business environment, stable teams cannot get the work done. States that what is needed, is flexible teamwork, i.e. gathering experts from far-flung locations and disciplines into temporary teams to tackle unexpected problems and identify emerging opportunities.